The Interface Stress Field in the Elastic System Consisting of the Hollow Cylinder and Surrounding Elastic Medium Under 3D Non-Axisymmetric Forced Vibration - Akbarov, Surkay D.; Mehdiyev, Mahir A. (TECH SCIENCE PRESS, 2018)
The paper develops and employs analytical-numerical solution method for the study of the time-harmonic dynamic stress field in the system consisting of the hollow cylinder and surrounding elastic medium under the non-axisymmetric forced vibration of this system. It is assumed that in the interior of the hollow cylinder the point-located with respect to the cylinder axis, non-axisymmetric with respect to the circumferential direction and uniformly distributed time-harmonic forces act. Corresponding boundary value problem is solved by employing of the exponential Fourier transformation with respect to the axial coordinate and by employing of the Fourier series expansion of these transformations. Numerical results on the frequency response of the interface normal stresses are presented and discussed.
Keywords: Interface stress field; frequency response; hollow cylinder; elastic medium; forced vibration; HALF-SPACE; TUNNEL; SURFACE; Computer Science; Materials Science